Environmental photocatalytic processes with POM. The photodecomposition of atrazine and photoreduction of metal ions from aqueous solutions - A. Hiskia; A. Troupis; E. Papaconstantinou (International Journal of Photoenergy)
Polyoxometalate anions (POM), resulting from the condensation of tungstate anions in strongly acidified solutions, can absorb efficiently light in the UV-near Vis region.The produced excited state is a very powerful oxidative reagent which can, mainly via OH radical attack, oxidize and mineralize a great variety of organic pollutants in aqueous solutions, while the photocatalytic circle is closed by reoxidation of the reduced POM, mainly, by O2. Metal ions can also serve as oxidants and close the photocatalytic cycle. In the process metal ions are reduced, precipitated and removed from the solution. Thus photocatalytic treatment for decontamination of waste waters from both organic and inorganic pollutants (metal ions) can be, in principle, achieved. POM+S→hνPOMred+SoxPOMred+Mn+→POM+Mred Atrazine, a widely used herbicide with s-triazine structure, is photodecomposed to cyanuric acid in presence of SiW12O404- in aqueous solutions. However, no precipitation of metal ions is obtained when atrazine is the sole organic substrate in aqueous solutions. The low solubility of atrazine produces insufficient concentration of reduced POM to cause precipitation.